PORTRAYING THE TRACT OF ISLAM IN EMPOWERING THE DYNAMICS OF THE POTENTIAL OF MARITIME NUSANTARA THROUGH THE SPICE ROUTE PERSPECTIVE - Sulistiono, Budi; Muchsin, Misri A. (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2022)
Abstract: The increasing influence of Islam in the archipelago was marked by the establishment of a number of sultanates. Based on the fact of the significant existence of the sultanate it is may indicate as evidence of political power. In the footsteps of Islam Nusantara, political power was achieved after great successes in building economic power, education, cultural-intellectual networks. Therefore, the stage of the traces of Islam Nusantara is not an event that is considered strange. Until the 17th century AD, there were even a number of sultanates on the islands of Java, Kalimantan, Sulawesi, Maluku, Papua, and Nusa Tenggara. The spread of the existence of a number of these sultanates in a relay as evidence of the results of the exemplary performances of a number of sultanates that had existed before. The approach used in this paper is a historical approach by utilizing study materials from historical literature. In compiling historical facts, it is guided by a logical framework arrangement according to chronological order. The conclusion is that, thanks to the wealth and social forces empowered by Muslim communities in various places in the archipelago, they can play political roles in political entities as evidenced by the birth of a number of Sultanates. This historical fact, at least strengthens Anthony Reid's theory, that the maritime economy is an indicator of maritime trade that unites trade routes with the formation of port cities as international trade routes.Keywords: empowerment, trade, maritime, Islamic Sultanate in the archipelago